Minimizing wind power curtailment using a continuous-time risk-based model of generating units and bulk energy storage - Nikoobakht, Ahmad; Aghaei, Jamshid; Shafie-khah, Miadreza; Catalão, J.P.S. (IEEE, 2020)
Wind power curtailment (WPC) occurs because of the non-correlation between wind power generation (WPG) and load, and also due to the fast sub-hourly variations of WPG. Recently, advances in energy storage technologies facilitate the use of bulk energy storage units (ESUs) to provide the ramping required to respond to fast sub-hourly variations of WPGs. To minimize the sub-hourly WPC probability, this paper addresses a generic continuous-time risk-based model for sub-hourly scheduling of energy generating units and bulk ESUs in the day-ahead unit commitment (UC) problem. Accordingly, the Bernstein polynomials are hosted to model the continuous-time risk-based UC problem with ESU constraints. Also, the proposed continuous-time risk-based model ensures that the generating units and ESUs track the sub-hourly variations of WPG, while the load and generation are balanced in each sub-hourly intervals. Finally, the performance of the proposed model is demonstrated by simulating the IEEE 24-bus Reliability and Modified IEEE 118-bus test systems.
Keywords: wind power curtailment; continuous-time unit commitment; Bernstein polynomials and energy storage; wind energy; risk management; optimisation; energy; wind farms; smart grids; modelling (creation related to information); energy production (process industry); effects (results); options (securities); fi=Sähkötekniikka|en=Electrical Engineering|